Escherichia fergusonii Associated with Pneumonia in a Beef Cow. (2nd December 2013) - Rimoldi, Guillermo M.; Moeller, Robert B.
Abstract : An adult Angus cow developed hyperthermia, prostration, and respiratory distress, dying 36 hours after the onset of clinical signs. The main finding during postmortem examination was a severe focally extensive pneumonia. Icterus and a chronic mastitis were also noticed. Histologic examination of the lungs detected fibrinonecrotic pneumonia, with large number of oat cells and intralesional Gram-negative bacterial colonies. Samples from lung lesions were collected, and a pure growth of Escherichia fergusonii was obtained. E. fergusonii is a member of Enterobacteriaceae, related to Escherichia coli and Salmonella sp. In veterinary medicine, E. fergusonii has been reported in calves and sheep with clinical cases suggestive of salmonellosis; in a horse and a goat with enteritis and septicemia; and in ostriches with fibrinonecrotic typhlitis. To our knowledge, this report represents the first description of E. fergusonii associated with an acute pneumonia in cattle.